A semitransparent particulate photoanode composed of SrTiO3 powder anchored on titania nanosheets. Issue 19 (9th August 2021) - Kageshima, Yosuke; Momose, Haruka; Takagi, Fumiaki; Fujisawa, Sora; Yamada, Tetsuya; Teshima, Katsuya; Domen, Kazunari; Nishikiori, Hiromasa
Abstract : A particulate semitransparent photoanode composed of SrTiO3 powder anchored on a titania nanosheets layer is developed. A tandem-type photoelectrochemical cell employing particulate photoanode and photocathode performed overall water splitting. Abstract : The development of semitransparent photoanodes is necessary to permit the construction of tandem-type photoelectrochemical (PEC) cells for water splitting in conjunction with an appropriate photocathode as the bottom cell. The fabrication of photoelectrodes from particulate material is especially desirable as a means of obtaining economically viable artificial photosynthetic systems. However, there have been no reports of efficient particulate semitransparent photoanodes applicable to tandem-type PEC cells. In this study, a particulate semitransparent photoanode composed of SrTiO3 (STO) powder anchored on a layer of titania nanosheets (TNSs) is demonstrated. The TNS layer functioned to anchor the particulate material and also served as a conductive layer. A tandem-type PEC cell combining a particulate semitransparent STO photoanode and a particulate Cu1.9 Sn0.38 Ge0.62 S3 (CTGS) photocathode as the top and bottom cells, respectively, successfully performed overall water splitting without an external bias voltage under simulated sunlight. The present study provides a novel and versatile methodology for the fabrication of semitransparent photoanodes from particulate photocatalytic material.